2005
DOI: 10.1037/0278-6133.24.1.22
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of "truth": How Counterindustry Campaigns Affect Smoking Behavior Among Teens.

Abstract: This study used structural equation modeling to test a theory-based model of the pathways by which exposure to the "truth" counterindustry media campaign influenced beliefs, attitudes, and smoking behavior in national random-digit-dial telephone surveys of 16,000 12-to 17-year-olds before, 8 months after, and 15 months after campaign launch. Consistent with concepts from the theory of reasoned action, youth in markets with higher levels of campaign exposure had more negative beliefs about tobacco industry prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 30 publications
1
76
1
Order By: Relevance
“…The Australian campaign used ads presenting personalized and graphic health consequences of smoking-called by some fear appeals ads (Hastings and MacFadyen 2002;Wakefield et al 1999). The mechanisms of action for industry manipulation ads have been most often explained by social-cognitive theories (e.g., psychological reaction, Brehm 1966, andsocial inoculation, McGuire 1964; also see Hersey et al 2005). In contrast, the mechanism of action underlying health consequences/fear appeals ads may be best theorized to be the elicitation of emotional arousal with subsequent conditioning and cognitive elaboration (see Biener and Taylor 2002;Lang 2000;National Cancer Institute 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The Australian campaign used ads presenting personalized and graphic health consequences of smoking-called by some fear appeals ads (Hastings and MacFadyen 2002;Wakefield et al 1999). The mechanisms of action for industry manipulation ads have been most often explained by social-cognitive theories (e.g., psychological reaction, Brehm 1966, andsocial inoculation, McGuire 1964; also see Hersey et al 2005). In contrast, the mechanism of action underlying health consequences/fear appeals ads may be best theorized to be the elicitation of emotional arousal with subsequent conditioning and cognitive elaboration (see Biener and Taylor 2002;Lang 2000;National Cancer Institute 2008).…”
Section: Introductionmentioning
confidence: 95%
“…12 In many cases, industry denormalization messages use specific quotes or images drawn from the industry in an effort to resonate with youths' concerns about being manipulated or exploited. 13,14 Industry denormalization gained widespread prominence following the success of the truth media campaigns in the United States, as well as a state-run campaign in California. 15,16 These campaigns gained notoriety for their engaging and, at times, confrontational nature, but also for their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this article explores how campaign evaluation, smoking status, and peer smoking interact to increase the likelihood of peer communication about the campaign, and whether these factors moderate the effect of campaign-related conversation on campaign outcomes. Other evaluations of ''truth'' have established that the campaign has successfully influenced youth smoking via its impact on proximal indicators of tobacco use such as beliefs, attitudes, and intentions (Davis et al, 2009;Farrelly et al, 2002;Hersey et al, 2005;Hersey et al, 2003). Specifically, the success of ''truth'' lies, at least in part, in its ability to influence beliefs and attitudes about deceptive tobacco industry practices.…”
Section: The Present Studymentioning
confidence: 97%
“…Specifically, longitudinal research has indicated that exposure to the ''truth'' campaign is protective in the progression to established smoking (Davis et al, 2009), and a dose-response relation between exposure and outcomes has been suggested (Farrelly et al, 2002). Some researchers have used the theory of reasoned action (Fishbein & Ajzen, 1975) as a framework for exploring the processes by which counterindustry messages influence youth smoking (Hersey et al, 2005;Hersey et al, 2003), demonstrating that exposure to counterindustry messages is associated with negative beliefs about tobacco industry practices and negative attitudes about the industry, which are, in turn, associated with less progression along a smoking continuum.…”
mentioning
confidence: 97%